2003
DOI: 10.1023/a:1025988519919
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: White laboratory male rats, inbred male C57BL/6 and Balb/c mice, and male Wistar rats, all previously divided on the basis of the type of emotional reactivity, were used to compare the effects of ten peptide compounds of the tuftsin family and Selank on the behavioral manifestations of emotional stress created by a conflict situation. Peptides were shown to have positive emotional effects and antistress actions. Individual physiologically significant effects were seen, due to the molecular structures of the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 2 publications
0
10
0
2
Order By: Relevance
“…Functional activity of CNS in hibernating animals during spring and fall is characterized by an imbalance between monoaminergic systems [2]. Monoamines serotonin, norepinephrine, and dopamine play a key role in the regulation of selective attention, learning, memory, and emotional resistance of animals and human to stress [4,9]. Administration of this heptapeptide produced a tranquilizing and stimulatory effects, improved emotional behavior, and normalized the ratio between monoamines in brain structures of Wistar rats treated neonatally with 6-hydroxydopamine.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional activity of CNS in hibernating animals during spring and fall is characterized by an imbalance between monoaminergic systems [2]. Monoamines serotonin, norepinephrine, and dopamine play a key role in the regulation of selective attention, learning, memory, and emotional resistance of animals and human to stress [4,9]. Administration of this heptapeptide produced a tranquilizing and stimulatory effects, improved emotional behavior, and normalized the ratio between monoamines in brain structures of Wistar rats treated neonatally with 6-hydroxydopamine.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of Pro-Gly-Pro group increased the resistance of the synthetic tuftsin derivative to adverse effects of external and internal factors [3]. Experiments on animals with genetically determined strategy of active or passive behavior in a stress situation demonstrated anxiolytic and nootropic properties of Selank [3,4,6]. Single administration of Selank induced long-term shifts in the concentrations of norepinephrine, dopamine, serotonin, and their metabolites in the brain of Wistar rats [4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The stress-induced increase in anxiety and decrease in orientation and exploratory activity were less pronounced after pretreatment with the peptides. At the same time, these peptides had no effect on behavioral activity of nonstressed animals [5,7]. In vitro experiments showed that PGP and GP produce a neuroprotective effect, protect rat pheochromocytoma PC12 cells from oxidative stress, and increase their survival [8].…”
mentioning
confidence: 99%
“…The taftsin group heptapeptide (Thr-Lys-Pro-ArgPro-Gly-Pro), whose pharmacological characteristics were studied at V. V. Zakusov Institute of Pharmacology, and selank, a psychotropic drug created on the basis of this heptapeptide at Institute of Molecular Genetics, Russian Academy of Sciences, normalize animal behavior and restore normal proportions of norepinephrine, dopamine, and serotonin in brain structures of adult rats exposed to antenatal hypoxia [1,3,4].…”
mentioning
confidence: 99%